Implementasi Mitigasi Penanggulangan Bencana Gempa Bumi di Kota Bukittinggi - Poppy Zahratul Fadhilah; Febri Yuliani (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Mitigation is a series of efforts to reduce disaster risk, both through physical development and awareness and improvement of the ability to face disaster threats. The purpose of this research is to find out and explain how the Implementation of Earthquake Disaster Mitigation and the inhibiting factors of the Bukittinggi City Regional Disaster Management Agency in implementing mitigation of earthquake disaster management. This research uses Edward III's theory which is divided into 4 (four) indicators, namely Communication, Resources, Disposition and Bureaucratic Structure. This research was conducted with descriptive qualitative research methods, data collection was obtained through interviews, observation and documentation. The results of this study indicate that the Implementation of Earthquake Disaster Management Mitigation in Bukittinggi cannot be said to be completely perfect or running optimally. The factors that hinder the Bukittinggi City Regional Disaster Management Agency are the lack of budget for disaster mitigation because it is affected by the city budget, inadequate facilities or facilities and infrastructure, lack of resources or experts in disaster risk reduction, officer skills still need further coaching. Based on the results and discussion, the researchers suggest that funding or budget from the government should be more concerned for the implementation of disaster mitigation including for earthquake mitigation, further increase resources in providing understanding to the community about the importance of disaster mitigation, and provide adequate facilities and infrastructure, provide understanding for the government through the education office to make mitigation or disaster management a subject in schools, provide notification from the region in the form of education ideally vulnerable points for evacuation and gathering points.